2023
DOI: 10.23736/s0021-9509.23.12589-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-center results of the Gore Excluder Conformable Endoprosthesis with active control system in endovascular aneurysm repair

Abstract: groningen, the netherlands; 2 department of surgical and integrated diagnostic sciences (disC), university of genoa, genoa, italy; 3 vascular and endovascular surgery unit, irCCs ospedale Policlinico san Martino, genoa, italy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…High technical success rates in patients with hostile anatomy managed with the conformable Gore device were also reported by Bonvini et al, 10 Lee et al 11 and Mascoli et al 12 However, these reports included a small number of patients (5, 24 and 25, respectively). A study by Zuidema et al 13 which included 64 patients also showed a 100% technical success rate using the CEXC device. In these four studies, no type Ia EL, type III EL or migration was seen.…”
Section: Discussionmentioning
confidence: 95%
“…High technical success rates in patients with hostile anatomy managed with the conformable Gore device were also reported by Bonvini et al, 10 Lee et al 11 and Mascoli et al 12 However, these reports included a small number of patients (5, 24 and 25, respectively). A study by Zuidema et al 13 which included 64 patients also showed a 100% technical success rate using the CEXC device. In these four studies, no type Ia EL, type III EL or migration was seen.…”
Section: Discussionmentioning
confidence: 95%
“…Although several series have shown favorable short-term outcomes using the device in angulated proximal necks (>60°), we have experienced challenges in our initial experience due to the lack of a support system using the proposed IFU technique, which can lead to inaccurate deployment. 10 , 11 , 12 , 13 Based on the proposed IFU and initial experience, it is recommended to use the Terumo Advantage wire due to the more flexible tip and to retract the ipsilateral sheath distal to the edge of the stent graft limb. However, the lack of stent graft support with excessive tortuosity and angulation can predispose to distal dislodgement and suboptimal deployment.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 8 , 9 The ability to bend and/or reposition the stent graft can extend the indications to patients with severely angulated proximal necks. 10 , 11 , 12 , 13 However, the initial investigators’ experience with the proposed instructions for use (IFU) revealed significant challenges due to risk of malposition and dislodgement of the stent graft in angulated segments. The aim of this case report is to illustrate a step-by-step modification of the proposed IFU for Gore Excluder Conformable stent graft deployment in a patient with a severely angulated proximal neck.…”
mentioning
confidence: 99%
“…W. l. gore and associates (flagstaff, aZ, usa) developed the excluder Conformable endograft with an active control system to increase flexibility and to expand the indication for use in hostile aortic neck anatomy. 17 The group of Zuidema 18 reviewed their singlecenter experience with this type of endograft, with focus on proximal apposition in challenging aortic necks.…”
Section: Sealing Zone Issues In Different Parts Of the Aortamentioning
confidence: 99%